N fertilizer and harvest impacts on bioenergy crop contributions to SOC. Issue 6 (3rd May 2016) - Stewart, Catherine E.; Follett, Ronald F.; Pruessner, Elizabeth G.; Varvel, Gary E.; Vogel, Kenneth P.; Mitchell, Robert B.
Abstract: Belowground root biomass is infrequently measured and simply represented in models that predict landscape‐level changes to soil carbon stocks and greenhouse gas balances. Yet, crop‐specific responses to N fertilizer and harvest treatments are known to impact both plant allocation and tissue chemistry, potentially altering decomposition rates and the direction and magnitude of soil C stock changes and greenhouse gas fluxes. We examined switchgrass ( Panicum virgatum L.) and corn ( Zea mays L., ) yields, belowground root biomass, C, N and soil particulate organic matter‐C (POM‐C) in a 9‐year rainfed study of N fertilizer rate (0, 60, 120 and 180 kg N ha −1 ) and harvest management near Mead, NE, USA. Switchgrass was harvested with one pass in either August or postfrost, and for no‐till (NT) corn, either 50% or no stover was removed. Switchgrass had greater belowground root biomass C and N (6.39, 0.10 Mg ha −1 ) throughout the soil profile compared to NT‐corn (1.30, 0.06 Mg ha −1 ) and a higher belowground root biomass C:N ratio, indicating greater recalcitrant belowground root biomass C input beneath switchgrass. There was little difference between the two crops in soil POM‐C indicating substantially slower decomposition and incorporation into SOC under switchgrass, despite much greater root C. The highest N rate decreased POM‐C under both NT‐corn and switchgrass, indicating faster decomposition rates with added fertilizer. Residue removal reduced corn belowground root biomass C by 37% and N by 48% and subsequently reduced POM‐C by 22% compared to no‐residue removal. Developing productive bioenergy systems that also conserve the soil resource will require balancing fertilization that maximizes aboveground productivity but potentially reduces SOC sequestration by reducing belowground root biomass and increasing root and soil C decomposition.